Developing a Framework for Guiding Blockchain Implementation in UAE Public Sector Based on Structuration and Actor Network Theories: A Qualitative Case Study Examination - ALROB, ALLAM MOHAMMAD (2023)
Blockchain is recognised as a radical technological innovation that will influence most sectors in the coming years as it is designed to exchange tangible and intangible assets in a secure distributed ledger. Focusing on the public sector, this study aimed to explore how the public sector can incorporate Blockchain to improve the quality of public sector services while considering the organisational and institutional structure. The research outcome is developing a framework to guide decentralised public sector e-services delivery. The study adopted subjectivist and interpretive philosophical stances and is based on two in-depth case studies of Blockchain implementation in two public sector entities in Dubai, United Arab Emirates. Data was collected through 38 semi-structured interviews in the two public sector entities. The data was gathered with relevance to implementing Distributed Ledgers Technology (Blockchain) applications. The study relied on seven conceptual propositions informed by two supporting theoretical frameworks: Actor-Network Theory (ANT) combined with Structuration Theory (ST), which allows researchers to achieve a better understanding of the socio-technical factors and aspects that are associated with and have an impact on the adoption process for Blockchain in public sector organizations.. The analysis of captured data in the two case studies was conducted using NVivo software and was underpinned by the seven conceptual propositions. The study’s findings make several contributions to the Information Technology Management field of study. This study has a theoretical contribution that is founded on the examination of how to combine Structuration and Actor-Network Theories in analysing the adoption of new technology. The study integrated both theories to develop a framework to guide decentralised public sector e-services delivery and help decision-makers in the public sector to appropriately determining how Blockchain implementation could be achieved in both sustainable and scalable manners. A practical contribution is found in increasing our understanding of how and why the public sector can adopt Blockchain to change the service delivery approach.